Dy doped SrTiO3: A promising anodic material in solid oxide fuel cells. (11th October 2018) - Singh, Saurabh; Singh, Prabhakar; Viviani, Massimo; Presto, Sabrina
Abstract: The perovskite-type oxides, having a general formula ABO3, are promising candidates for anode materials in solid oxide fuel cells. In particular, doped SrTiO3 based perovskites are potential mixed ionic-electronic conductors and they are known to have excellent thermal and chemical stability along with carbon and sulfur tolerance. In this work, Dyx Sr1-x TiO3-δ system with x = 0.03, 0.05, 0.08 and 0.10 is studied to understand the influence of Dy content on its structural and electrical behavior. Electrochemical properties are measured, both in air and hydrogen atmosphere, and structural characterizations are performed before and after electrochemical tests and compared each other to study the stability. Results show that Dyx Sr1-x TiO3-δ powders with x ≤ 0.05, are single phase, while for x ≥ 0.08 a small amount of secondary phases is formed. In air, the conductivity is predominantly mixed ionic-electronic type for x ≤ 0.05, becoming ionic for x ≥ 0.08. It is observed that conductivity, for each composition, increases passing from air to hydrogen and activation energy decreases. Dy0.05 Sr0.95 TiO3-δ shows the highest conductivity in air whereas Dy0.08 Sr0.92 TiO3-δ in H2 atmosphere. Degradation observed by XRD is negligible for x ≤ 0.05 but increases with higher Dy content. Graphical abstract: Highlights: Dyx Sr1-x TiO3-δ system was studied as candidate for anode in a SOFC. Structural and electrical properties were studied in air and hydrogen. Degradation after reduction is negligible for x ≤ 0.05. Dy0.08 Sr0.92 TiO3-δ showed the highest conductivity in H2 .